Distributed control of active and reactive power for photovoltaic systems in a high penetrated grid (2016)
The need to reduce greenhouse gases emission has encouraged the introduction of Photovoltaic (PV) generators into electrical grid. However a high penetration of PV system in a distribution network produce deviations in the quality of the electrical power. This research propose a distributed hierarchical control system in order to keep the power quality in its accepted values. To accomplish this goal, the control scheme must face geographically dispersed and nonhomogeneous actuators in a complex network. These challenges are addressed using game theory and consensus algorithm in the design of the control. It is tested via simulation using DIgSILENT PowerFactory. The results of the simulations show that the control system is able to keep the voltage and frequency very close of the required values. In conclusion the design of the adequate control system allow to increase the penetration of renewables energies into the electrical grid, keeping the power quality